Psychometric properties of the Portuguese version of the cognitive emotion regulation questionnaire - kids version (CERQ-kids) among a sample of children and adolescents exposed to wildfires - Moreira, Helena (2020)
The Cognitive Emotion Regulation Questionnaire-Kids (CERQ-Kids) is a self-report questionnaire that assesses cognitive emotional regulation strategies that children may employ when they face traumatic or stressful events. However, its psychometric properties were only analyzed among participants from the general community. The goal of this study is to examine the factor structure of the Portuguese CERQ-Kids and to explore its psychometric properties in a sample of children/adolescents exposed to a potentially traumatic event (wildfires). The sample included 488 children/adolescents (Mage = 13.02, SD = 2.5, range = 8–17) who lived in the areas affected by the 2017 Portugal wildfires and who did not receive a diagnosis of a mental disorder, and a clinical group of 50 children/adolescents (Mage = 12, SD = 2.62, range = 8–16) who lived in the same areas and who were diagnosed with a mental disorder. All participants completed the CERQ-Kids and measures of emotion regulation strategies, mental health, and quality of life. The best fitting model was the original nine-factor correlated model. This model was invariant across gender and age groups. With the exception of the Acceptance subscale, the remaining subscales presented adequate internal consistency. Participants from the clinical group scored higher on Self-blame, Rumination, Catastrophizing, and Acceptance than participants from the non-clinical group. Significant correlations were found between the CERQ-Kids subscales and measures of cognitive reappraisal, expressive suppression, prosocial behavior, mental health, and quality of life. The Portuguese version of the CERQ-Kids proved to be a psychometrically adequate measure of cognitive emotion regulation strategies that children and adolescents may use when exposed to a potentially traumatic event.